Ethnomusicology Matters Influencing Social and Political Realities (Edition 1) - Kölbl, Marko; Saglam, Hande; Hemetek, Ursula (2019)
This book gathers international voices from the field of ethnomusicology discussing the socio-political relevance of the discipline. The articles draw from contemporary discourses that take into account the role of music and dance in shaping social and political realities. An important field connected to political relevance is heritage, either in connection with the UNESCO or with archives. Ontologies of indigenous groups and their relevance in knowledge production is discussed in ethnomusicology nowadays as well as the possibilities of decolonising the discipline. Two articles from ethno-choreology explore dance from the gender perspective and in the post-socialist political structures. Different approaches from applied ethnomusicology deal with social justice, participatory dialogical practice, and the socio-political relevance of performance. Forced migration is seen as comprehensive topic for future ethnomusicology. The contents of the book mirror influential discourses of ethnomusicology today that will definitely shape the future development of the discipline.